2000
DOI: 10.1021/jf9911085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Hydrostatic Pressure on the Strawberry Anthocyanins

Abstract: Color stability of fruit juice made from strawberries (Fragaria x ananassa, cv. Elsanta) that were subjected to high hydrostatic pressure was studied by measuring the anthocyanin content. High hysrostatic pressure is a method of preservation of food alternative to heat treatment. It is therefore essential to assess the impact of high pressure on color molecules. Samples were pressurized under 200, 400, 600, and 800 MPa for 15 min at a temperature controlled between 18 and 22 degrees C. After application of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 4 publications
4
62
0
4
Order By: Relevance
“…Polyphenol oxidase is one of the major oxidative enzyme involved in browning reactions, affecting the colour and flavour of food products (Zabetakis et al, 2000). Changing to brown colour affects the appearance and organoleptic properties of the products.…”
Section: Ppo Inactivationmentioning
confidence: 99%
“…Polyphenol oxidase is one of the major oxidative enzyme involved in browning reactions, affecting the colour and flavour of food products (Zabetakis et al, 2000). Changing to brown colour affects the appearance and organoleptic properties of the products.…”
Section: Ppo Inactivationmentioning
confidence: 99%
“…In contast to these findings, Terefe et al (2013) and Talcott et al (2003) showed significant loss of anthocyanins in strawberry puree and muscadine grape juice. (Chen et al, 2013;Zabetakis et al, 2000;Ferrari et al, 2011, Barba et al, 2011. Significantly higher loss of anthocyanins in HHP-treated cloudy strawberry juices were observed than in HHPtreated clear strawberry juices at 4°C storage, which was possibly due to higher concentrations of oxygen absorbed on pulp particles promoting the degradation of anthocyanins.…”
Section: Effects Of Hhp On Anthocyanin Content Of Fruit and Fruit Promentioning
confidence: 99%
“…El contenido de pigmentos antocianos presente en la fresa fresca fue de 34±5 mg pelargonidina 3-glucósido/100 g muestra fresca. Este valor es similar a los reportados en otros estudios realizados en fresa de la misma variedad (Zabetakis et al, 2000;Pérez y Sanz, 2001;Castro et al, 2002).…”
Section: V244 Determinación Del Volumen De Las Muestrasunclassified